Graphene-Insulator-Semiconductor Junction for Hybrid Photodetection Modalities. Issue 1 (December 2017) - Howell, Stephen; Ruiz, Isaac; Davids, Paul; Harrison, Richard; Smith, Sean; Goldflam, Michael; Martin, Jeffrey; Martinez, Nicholas; Beechem, Thomas
Abstract A sensitive optical detector is presented based on a deeply depleted graphene-insulator-semiconducting (D2 GIS) junction, which offers the possibility of simultaneously leveraging the advantages of both charge integration and localized amplification. Direct read-out and built-in amplification are accomplishedvia photogating of a graphene field-effect transistor (GFET) by carriers generated within a deeply depleted low-doped silicon substrate. Analogous to a depleted metal-oxide-semiconducting junction, photo-generated charge collects in the potential well that forms at the semiconductor/insulator interface and induces charges of opposite polarity within the graphene film modifying its conductivity. This device enables simultaneous photo-induced charge integration with continuous "on detector" readout through use of graphene. The resulting devices exhibit responsivities as high as 2, 500 A/W (25, 000 S/W) for visible wavelengths and a dynamic range of 30 dB. As both the graphene and device principles are transferrable to arbitrary semiconductor absorbers, D2 GIS devices offer a high-performance paradigm for imaging across the electromagnetic spectrum.